Aktualisasi Praktik Keagamaan Melalui Program Penyelengaraan Jenazah di Kelurahan Antang Kota Makassar - Fauziah Ramdani (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2022)
The purpose of the STIBA Makassar Real Work Lecture (KKN) Batch IV is as a form of community service which is a pillar of the Tridharma of Higher Education, especially in teaching Arabic as the main program. The method of implementing the service program begins with mapping the problems and needs of the community using SOAR analysis. After the analysis is done, a work program that is appropriate and needed by the community is drawn up. After the analysis is carried out, a work program that is appropriate and needed by the community is prepared. One of the work programs that have been successfully carried out is the funeral management program. This program is running well and has shown results that are in line with the objectives of the STIBA Makassar Student Community Service Program, namely increasing Islamic knowledge of the Antang village community, especially regarding the process of organizing corpses. The result achieved is that more and more people in the Antang village understand and can practice how to organize a corpse if someone dies.